Analisis Komparasi ISO 11620:2014 dan ISO 11620:2023 sebagai Standar Indikator Kinerja Perpustakaan - Muhammad Bahrudin (Media Pustakawan, 2023)
ISO 11620 is an international standard used as a guideline for measuring library performance. In 2023, this standard underwent a significant revision with the addition of library performance indicators. This study aims to understand the differences occurrs in both editions of the ISO 11620 standard and the implications of these changes in library performance measurement. This study used a comparative descriptive approach to analyze the differences and similarities between ISO 11620:2014 and ISO 11620:2023. The Online Draftable was used to analyze the text comparison. The results of the text comparison analysis identified 4,541 content changes and 317 text style changes in ISO 11620:2023. There is a change in the number of terms and definitions covered in ISO 11620:2014 from 57 terms to 85 terms and definitions in ISO 11620:2023. The number of performance indicators in ISO 11620:2014 was 52, and in ISO 11620:2023 it is 85. There are 15 new performance indicators focus on library use and utilization including collections, access via mobile devices, library awareness, and library impact assessment.